2015
DOI: 10.14254/2071-789x.2015/8-1/24
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of social networks in modern digital library environment

Abstract: Abstract. Th e article examines the concept of social networking, implementation of the information communication technologies in the social network procedures, formation of online social networks. Observed implementation of these technologies in establishment of the modern digital libraries and presented possible perspectives of the social digital library formation. Also was described the solution of some tasks using fuzzy sets theory and bibliometric methods for control of library management by analyzing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Por sua vez, Alguliyev et al (2015) trabalham o conceito de bibliotecas digitais, que consistem em compartilhamento, troca, relacionamento, cooperação, o que revela os aspectos sociocêntricos e sociotécnicos desse ambiente. Ao aceitar como fato que essa inteligência é valorizada e distribuída por toda parte, Lévy propõe que passemos do fato ao projeto:…”
Section: Para Mondiniunclassified
“…Por sua vez, Alguliyev et al (2015) trabalham o conceito de bibliotecas digitais, que consistem em compartilhamento, troca, relacionamento, cooperação, o que revela os aspectos sociocêntricos e sociotécnicos desse ambiente. Ao aceitar como fato que essa inteligência é valorizada e distribuída por toda parte, Lévy propõe que passemos do fato ao projeto:…”
Section: Para Mondiniunclassified
“…Por sua vez, Alguliyev et al (2015) trabalham o conceito de bibliotecas digitais, que consistem em compartilhamento, troca, relacionamento, cooperação, o que revela os aspectos sociocêntricos e sociotécnicos desse ambiente.…”
Section: Para Mondiniunclassified
“…Consistent to this statement, [15] has concluded that participation as the important aspect in social capital is very determining to organizational quality. The study on social network done by [16], has shown that social network is very influential to the change of social behavior perspective among individuals. The agreements made by farmers with traders were subjected to the study by [17], and they found that agreements between farmers and entrepreneurs were related closely with village isolation and personal profile.…”
Section: Economic Sociology Approach Inmentioning
confidence: 99%